DIGITAL DISINFORMATION AND ELECTORAL LAW: CHALLENGES AND SOLUTIONS TO STRENGTHEN THE LEGITIMACY OF ELECTIONS - Araujo, Isadora; Campos, Samuel; Amorim, Ana Clara; Sousa , Bruno; Moraes , Maria Rita; Coelho, Bianca; Campos, Gabriella Campos; Rodrigues, Letícia; Ferreira, Valdivino (CIPEEX, 2025)
The research analyzes how disinformation spreads rapidly on social media during Brazilian elections, affecting voters’ trust and intensifying polarization. Algorithms that prioritize content confirming preexisting beliefs create “information bubbles,” expanding the reach of fake news and undermining the integrity of the electoral process. The study aims to understand how digital disinformation challenges the legitimacy of the electoral process in Brazil and, based on this analysis, to suggest recommendations that strengthen democracy. A qualitative approach was used, based on a systematic literature review and an interpretive analysis of emblematic cases of false-news propagation. This methodology made it possible to identify dissemination mechanisms and the impacts of digitalmanipulation strategies. The combination of automated accounts (bots) and human operators (trolls) creates the appearance of spontaneous engagement but, in reality, promotes the amplification of distorted narratives. Furthermore, the Brazilian electoral legal framework proves to be outdated in the face of technological innovations, revealing a lack of real-time auditing and transparency in the circulation of information, especially within private communication channels. To restore the credibility of electoral contests, the study proposes updating the regulation of digital platforms with continuous audits and graduated sanctions, implementing media literacy campaigns, and strengthening cooperation among the Judiciary, electoral authorities, and civil society.